TRADE AND ENVIRONMENT IN INDONESIA: CASE STUDY OF ASEAN-CHINA FREE TRADE AGREEMENT - Azizurrohman, Muhammad; Hartarto, Romi Bhakti (Jurnal Ekonomi & Studi Pembangunan, 2019)
In recent decades, the debate about the impacts of economic globalization through free trade has become attention to public policy. One important issue to address is related to environÂmental quality. It has been fifteen years since ASEAN-China Free Trade Agreement (ACFTA) was firstly signed and the total trade flows between ASEAN countries and China have grown around US$ 20 billion per year. Under the ACFTA commitment, tariff rates for exports from China to ASEAN countries have been reduced gradually and so have the tariff rates of ASEAN exports to China. This paper attempts to investigate whether expanded trade causes environmental damage in Indonesia. As the main largest economy in ASEAN, Indonesia has greatly contributed to the pollution released in ASEAN area. Using industrial pollution projection system developed by World Bank in 1995, it has been found that the estimated amounts of pollution have been inÂcreasing by approximately five times in Indonesia after fifteen years of ACFTA implementation. Even though the share of export of most polluting sectors has been decreasing, its contribution on the pollution intensity remains the largest. Since chemicals become the most polluting sector with its rapid growing in export to China, this sector needs to be considered in trade negotiations in order to lessen negative impacts of trade to the environment.